Diagnosis and treatment of hyperfiltering blebs - Cronemberger,Sebastião (2011)
PURPOSE: To report on a new treatment for hyperfiltering bleb as well as its diagnostic criteria. METHODS: Twenty eyes with hypotony due to hyperfiltering bleb caused by trabeculectomy with mitomicin C were treated with bleb resection. The diagnosis of hyperfiltering bleb followed these criteria: intraocular pressure lower than six mmHg (Goldmann tonometer); no inflammation in the anterior segment; presence of an elevated and/or diffuse and avascular bleb with or without microcysts; negative Seidel test; no ciliochoroidal detachment found with ultrasound biomicroscopy. We registered the following data pre and post operatively: type of glaucoma, visual acuity, bleb aspect and fundoscopic findings. A successful resolution of hypotony was achieved when intraocular pressure ranged from six to 14 mmHg with or without antiglaucomatous medication. RESULTS: At a minimum follow-up of 19 months ocular hypotony had been reversed in all eyes. At the last exam, intraocular pressure varied from eight to 14 mmHg in 18 (90%) eyes; 12 (66.7%) eyes had no medication and six (33.3%) used antiglaucomatous medication. In two (10%) eyes, another trabeculectomy was necessary to control intraocular pressure. Hypotonic maculopathy developed preoperatively in seven eyes and was reversed after bleb resection. Visual acuity improved in 15 (75%) eyes but did not change in five (25%). CONCLUSION: Bleb resection is a safe and adequate treatment for ocular hypotony due to hyperfiltering bleb. It also restores vision in a considerable number of patients. The diagnosis of hyperfiltering bleb must follow rigorous criteria.